1993
DOI: 10.2307/1591651
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Interaction of Eimeria meleagrimitis with Hemorrhagic Enteritis Virus or Marble Spleen Disease Virus in Turkeys

Abstract: The interaction of Eimeria meleagrimitis with hemorrhagic enteritis virus (HEV) or marble spleen disease virus (MSDV) was studied in 4-week-old female turkeys. Birds given either virus in combination with the coccidia showed greater weight gain than did birds given HEV alone. A combination of MSDV and E. meleagrimitis resulted in significantly lower oocyst production when oocysts were counted from individual birds. Levels of serum glucose, serum albumin, and total protein were reduced in birds given HEV either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
(1 reference statement)
3
5
0
Order By: Relevance
“…This coincides with the observation of Norton et al (1993), where birds receiving EM with HEV experienced an amelioration of the weight loss which occurred in birds receiving HEV alone. This trend was also seen in the antigen titre in which there was a numerical drop in both the mean titre and the percentage of responders.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This coincides with the observation of Norton et al (1993), where birds receiving EM with HEV experienced an amelioration of the weight loss which occurred in birds receiving HEV alone. This trend was also seen in the antigen titre in which there was a numerical drop in both the mean titre and the percentage of responders.…”
Section: Discussionsupporting
confidence: 88%
“…Previous work in this laboratory has indicated that 4-week-old poults have lost maternal antibody and are susceptible to challenge. The experimental procedure has been described in detail (Norton et al, 1993) and therefore only the essential points are given here.…”
Section: Birds and Experimental Proceduresmentioning
confidence: 99%
See 3 more Smart Citations